Hubungan Pendidikan dan Pekerjaan Ibu dengan Pemakaian Alat Kontrasepsi Dalam Rahim (AKDR) - Lia Hartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine whether there was a relationship between education and occupation of the mother with the use of contraceptive devices in the womb at the Taba Puskesmas Lubuklinggau in 2019. The research method used an analytical survey method with a cross sectional approach. Univariate analysis results obtained from 50 acceptors revealed that a small proportion of respondents did not use contraceptive IUD as many as 9 respondents (18%), respondents in the education category most respondents were educated as many as 30 respondents (60%) in the occupational category (having good jobs) totaling 22 respondents (44%). In conclusion, there is a significant relationship between mother's education and the use of the IUD. no relationship between maternal occupation and IUD use was not statistically proven. Keywords: Employment, IUD Use, Education